(3cJGH aj GdWHs
(3ChdgG (B:s
(3HGH aj GdTYQ HGQO jGHS aj eRGLg, jYQV dg ef GdCeQGV KdGKI CeQGV, GdJTbb hGdSbhW s
(3BNQgG (B:s
(3COhjI GdebYOI UaI eQge GdfGUQ ,RfLGQ hbdi hLjQ GdMLQ ef cd hGMO OQgeGf hjSJYed Ydi GdfGUhQ agh HQA dg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B70 - (3U(B131s
(3GdfSNI HgG MhGTs
(3GfXQ eY JMUjd ZQV GdbGUO Qbe (B"44(3, (B362" s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B198 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs